Stress distribution in bone simulation model with pre-angled implants - Goiato, Marcelo Coelho [UNESP]; Arsufi, Guilherme Sarauza; de Medeiros, Rodrigo Antonio; Pesqueira, Aldiéris Alves [UNESP]; Guiotti, Aimée Maria [UNESP]; Santos, Daniela Micheline dos [UNESP] (Taylor & Francis, 2015)
The aim of this study was evaluate the biomechanical behaviour of prostheses screwed into conventional (0° angulation) and pre-angled experimental (8, 12 and 20°) external hexagon implants (13 × 4 mm) by photoelastic analysis. Eight casts were made in photoelastic resin. Casts were divided into groups of single crowns or three combined elements. Each unit was positioned in a circular polariscope. By using a universal testing machine, 100 N loads were applied in the axial and oblique (45°) directions to fixed points on the occlusal surfaces of the crowns. Generated stresses were recorded photographically and analysed qualitatively in a graphics program. In single-element prostheses, the number of high-stress fringes increased with increasing implant angle. However, in three-element prostheses, there was no difference in the stress distribution with implant angle, except for the 12° implant that had a higher degree of stress. For the other groups pre-angulation of the implant increases the concentration and intensity of stresses for single prosthesis and has similar stress distribution in three-element fixed prostheses.
Keywords: Dental implants; Dental prosthesis; Implant-supported; Photoelastic analysis